Discovering students’ preference for grammar learning activities outside the classroom / Tuan Sarifah Aini Syed Ahmad, Anealka Aziz Hussin and Ghazali Yusri - Syed Ahmad, Sarifah Aini; Hussin, Anealka Aziz; Yusri, Ghazali (Universiti Teknologi MARA Cawangan Kedah, 2018)
Learning grammar is crucial to improve students’ linguistic competence. However, face-to-face time is limited for engaging students in learning grammar in the classroom. Therefore, students are normally encouraged to participate in grammar learning activities outside the classroom. This paper examines types of grammar learning activities that students prefer to do outside the classroom, types of grammar learning activities that students have done voluntarily for practicing grammar outside the classroom, and whether online grammar games on the Internet is easy to obtain and suitable for the students’ course. The sample of the study was 110 predegree students aged 18 years old. The data gathered by using a questionnaire and analyzed by using Microsoft Excel 2013.